HUBUNGAN MOTIVASI BERPRESTASI DENGAN KEMANDIRIAN BELAJAR SISWA KELAS 11 DI SMK PGRI 2 SALATIGA - Nindita Avelolang; Tritjahjo Danny Soesilo; Adhi Krisna Maria Agustin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Achievement motivation is one of the important factors that encourages students to achieve success in the learning process. Students with high achievement motivation tend to be more active, responsible, and capable of developing independent learning skills. This study aimed to determine the relationship between achievement motivation and learning independence among eleventh-grade students at SMK PGRI 2 Salatiga. This study employed a quantitative approach with a correlational research design. The population consisted of 125 eleventh-grade students, and the sampling technique used was total sampling, in which the entire population was selected as the research respondents. Data were collected using Likert-scale questionnaires that had met validity and reliability requirements. Data analysis was conducted using Spearman Rank correlation analysis. The results showed a positive and significant relationship between achievement motivation and learning independence, with a correlation coefficient of 0.750 (p < 0.01), which was categorized as strong. The findings indicate that higher achievement motivation is associated with higher levels of learning independence among students.